Georreferenciación del humedal la tembladera empleando la herramienta SIG en el sistema operativo Windows 10 - Reyes Barros, Juan Fernando (My University, 2020)
The situation of wetlands around the world is alarming due to problems such as deforestation, expansion of agricultural frontiers and the excessive use of water contribute to the significant reduction of their conservation areas. Due to this, the objective was to update the geospatial information of the main lagoon of the La Tembladera wetland and provide updated data with the georeferencing of the study area. Using practical tools such as precision GPS, which, added to Geographic Information Systems GIS and different Softwares present in Windows operating systems such as Google Earth, Google Satellite, and programs such as ArcGis allowed the gathering of geospatial information in a precise way. The methodology used was based on the application of the logical-deductive-method for the collection of information from secondary sources, which by reviewing different scientific articles according to the subject matter, obtained from a database such as EBSCO, provided accurate information. on the state of the wetlands, and on current methods for georeferencing such as that used by Quintana Cruz and López Sánchez. In addition to them, information was collected from primary sources, by taking coordinates in the wetland, in order to have a precise geospatial location of the same and to be able to execute the graphing of the data in the GIS.
La situación de los humedales alrededor del mundo es alarmante debido a problemas como la deforestación, expansión de las fronteras agrícolas y el uso desmedido del agua contribuyen a la reducción significativa de sus áreas de conservación. Debido a esto se propuso como objetivo actualizar la información geoespacial de la laguna principal del humedal La Tembladera y proporcionar datos actualizados con la georeferenciación del área de estudio. Usando herramientas prácticas como GPS de precisión, que sumado a los Sistemas de Información Geográfica SIG y diferentes Softwares presentes en los sistemas operativos Windows como Google Earth, Google Satelite, y programas como ArcGis permitió el levantamiento de información geoespacial de manera precisa. La metodología usada se basó en la aplicación de método-deductivo-lógico para la recolección de información desde fuentes secundarias, mismas que mediante la revisión de diferentes artículos científicos acordes a la temática tratada, obtenidos desde una base de datos como EBSCO, proporcionaron información precisa sobre el estado de los humedales, y sobre métodos actuales para la georreferenciación como el usado por Quintana Cruz y López Sánchez. Sumado a ellos se recolectó información desde fuentes primarias, mediante la toma de coordenadas en el humedal, para así tener una ubicación geoespacial precisa del mismo y poder ejecutar la graficación de los datos en los SIG.
Keywords: GEORREFERENCIACION; HUMEDAL; LA TEMBLADERA; HERRAMIENTA SIG